Praktik insider trading sebagai bentuk pelanggaran prinsip keterbukaan informasi dalam pasar modal di Indonesia - Fisuda Alifa Mimiamanda Radinda; Monika Ardia Ningsi Massora; Ricka Auliaty Fathonah (University of Merdeka Malang, 2020)
This study discusses the legal protection of investors against the practice of insider trading in the capital market in Indonesia and violations / crimes of insider trading is a form of violation of the principle of information disclosure in the capital market. The purpose of this study is to analyze the legal protection of investors against the practice of insider trading in the capital market in Indonesia and violations / crimes of insider trading is a form of violation of the principle of information disclosure in the capital market. This research uses the normative juridical method. The approach used is the Invitation-invite approach. The legal material used is primary legal material and secondary legal material. Legal material collection techniques used through library studies. Technical analysis used with deductive logic, which draws conclusions from general to specific. The results of the study are difficult to provide a legal protection for investors due to Insider Tranding practices, due to weaknesses in the Capital Market Law for the enforcement of insider trading practices in the Capital Market and Insider Trading is a form of violation of the principle of information disclosure in the Capital Market, even though the purpose of the principle of information disclosure itself is to guarantee transparency in the capital market.How to cite item: Mimiamanda Radinda, F., Ningsi Massora, M., Fathonah, R. (2020). Praktik insider trading sebagai bentuk pelanggaran prinsip keterbukaan informasi dalam pasar modal di Indonesia. Jurnal Cakrawala Hukum, 11(1), 41-49. doi:https://doi.org/10.26905/idjch.v11i1.3528